On optimal use of radiation in cardiological procedures - Järvinen, Jukka (fi=Turun yliopisto|en=University of Turku|, 2020)
In this thesis, the use of radiation in contemporary interventional cardiology (IC) has been investigated. The focus of the study is on patient doses in various minimally invasive procedures with higher doses. Patient exposure to radiation can be measured with Kerma area product (KAP) and its diagnostic reference levels (DRLs), maximum skin dose (MSD) and absorbed organ doses. In this thesis, all three doses are explored with accurate and repeatable methods and curiosity toward the causes behind the dose level variation. KAP results show that the highest patient doses in IC occur in transaortic valve implantations (TAVIs) and percutaneous coronary interventions (PCI) with significant variation between hospitals and countries. In TAVIs, this variation is partly due to the novelty of the procedure, but in PCIs, the need for difficulty levels in the DRLs is apparent. The machine learning methodology used in this thesis provides insight into how such difficulty levels can be determined and what kinds of features they should be comprised of. The MSD measurements performed with Gafchromic films show significantly higher dose levels in TAVIs than in other procedures and KAP and air kerma alert levels were proposed accordingly in Publication 3 of this thesis. The MSD levels show a high variance between hospitals and local DRLs were calculated for two of the participating hospitals. With the observed variation in respect to both KAP and air kerma, a good alternative to these alert levels are automatic skin dose estimations provided by the angiosystem manufacturers. In this work, two such algorithms were compared to the measured doses and the results were very promising. Heart organ dose was measured with radiophotoluminescence (RPL) dosimeters and an anthropomorphic phantom in both a computed tomography (CT) scan routinely performed before a TAVI procedure and in a typical TAVI procedure. The results show that a majority of the dose is caused by the CT scan and that the dose from the procedure is relatively low compared to other published results. In total, the thesis illustrates good investigative practices in radiation protection, their application to IC and results that benefit both contemporary cardiology and physicists working in the field.